Building resilient cities in China : the nexus between planning and science : selected papers from the 7th International Association for China Planning Conference, Shanghai, China, June 29-July 1, 2013 /: the nexus between planning and science : selected papers from the 7th International Association for China Planning Conference, Shanghai, China, June 29-July 1, 2013. ([2015]) - Unknown
No abstract available